Auditing learning management system using information technology infrastructure library (ITIL) - Parmonangan R Togatorop (Jurnal Mantik, 2023)
Information security is an important asset in the organization so that the confidentiality, integrity and availability of information must be maintained. One way to do this evaluation is to conduct an audit. Audit is an evaluation process to ensure the level of suitability between a system and predetermined criteria. In this paper, an audit will be carried out on the security of IT services at the Del Institute of Technology. Service audits are conducted to determine the level of security of information technology services used. This audit was conducted using a framework called ITIL (Information Technology Infrastructure Library). ITIL is a framework that functions to manage business services and IT infrastructure with the aim of ensuring that the quality of IT services is in accordance with the criteria. This audit was carried out using data from a questionnaire given to several students of the Del Institute of Technology, where this questionnaire contains five subdomains that will be analyzed to determine whether the security of the services is good or not. It can be concluded that the LMS has implemented service operations properly. The output of this research is a recommendation to further improve the security of IT services.